PROSES MANUFAKTUR SPUR GEAR CUTTER MENGGUNAKAN MESIN FRAIS UNIVERSAL KNEE MILLING MODEL 57-3C - Ratlalan, Roberth Marshall; Arhan, Muhammad (Badan Penerbit Universitas Muria Kudus, 2026)
Spur gears are essential components in power transmission systems and are widely used in various mechanical applications. As industrial needs evolve, the use of engineering polymer materials such as Teflon has become an attractive alternative due to their low coefficient of friction, good chemical resistance, low noise levels, and light weight. This study aims to study the manufacturing process for a Teflon (PTFE) spur gear cutter using a Knee Milling Machine Model 57-3C universal milling machine and to evaluate the resulting product's quality control methods. The method used involves several stages: gear dimension design, material and tool preparation, machining parameter settings, tooth formation using a modular milling cutter and dividing head, and finishing, spline groove creation, and threading. Quality control is performed through dimensional measurements using calipers and visual inspection to detect surface defects, cracks, and deformation caused by the cutting process. The results show that a Teflon spur gear cutter with 45 teeth and a module of 2.5 can be manufactured satisfactorily using a universal milling machine. All main dimensions measured are within a tolerance of ±0.20 mm, and no significant defects were found during visual inspection. This shows that the universal milling machine Knee Milling Machine Model 57-3C can be used effectively for manufacturing spur gears made of engineering polymers with an adequate level of accuracy. Keyword : Spur gear, Teflon (PTFE), Knee Milling Machine Model 57-3C, Dividing head, Quality Control.